IMPLEMENTATION OF THE E-COMMERCE PLATFORM TO IMPROVE TECHNOLOGY ADAPTATION IN MSMES - Pandu Adi Cakranegara; Muhammad Mujtaba Mitra Zuana; Ellya Sestri; Bambang Surahman; Kurniawansyah Kurniawansyah (SEAN Institute, 2022)
In the digital age, every consumer will select online sales because it is the thing that people are currently most interested in, as it can be accessible from anywhere and at any time as long as they have an internet connection. Customers benefit from the convenience of online shopping because they do not have to travel to the business location to pick up their purchases. In reality, the marketing processes of most micro, small, and medium-sized enterprises (MSMEs) continue to rely on manual transaction processing mechanisms for direct purchases and on conventional transaction recording methods. Implementing an e-commerce information system for MSMEs so that it is easier for MSMEs and customers to conduct online transactions and MSMEs can adapt to the digital era is a research objective aimed at addressing the inadequacy of MSMEs in adapting to information technology. The results of the study indicate that the system features in e-commerce are adapted to the analysis of user needs, i.e., there are product features, ordering features, transaction detail features, and report features that facilitate product purchase transactions through the e-commerce system so that there are superior features of the system to improve quality MSME services and maintain customer loyalty in order to conduct online transactions. Blackbox testing was conducted for five system functionality testing scenarios throughout the system testing phase, with the result that the entire system performed as expected and in compliance with user requirements.